Can Interactive PowerPoint Media Revolutionize Simple Sentence Learning in Elementary Schools? - Rifana Khoirunnisa; Widagdo, Arif (Universitas Hamzanwadi, 2024)
Improving student outcomes in constructing simple English sentences is essential, particularly in elementary education, where foundational language skills are developed. In Indonesian elementary school, low performance in this area was linked to the lack of interactive learning media. This study aimed to address this gap by developing, assessing the feasibility of, and evaluating the effectiveness of interactive PowerPoint-based learning media for fourth-grade students. Using the ADDIE development model—comprising Analysis, Design, Development, Implementation, and Evaluation—the study involved 26 students from SDN 02 Kendengsidialit Jepara, with data collected through observations, interviews, questionnaires, and documentation. The findings revealed a significant improvement in student performance, with the maximum score increasing from 71 in the pretest to 88.89 in the post-test. This improvement was confirmed by a paired t-test validating the media's effectiveness in enhancing learning outcomes. The analysis of pretest and post-test data further indicated moderate overall improvement underscoring the positive impact of the interactive PowerPoint-based learning approach. The study demonstrated that the interactive PowerPoint media is practical and feasible for improving students' mastery of simple English sentences. It is a valuable tool for enhancing language instruction in primary education.